Autophagosome–lysosome fusion in neurons requires INPP5E, a protein associated with Joubert syndrome. (23rd June 2016) - Hasegawa, Junya; Iwamoto, Ryo; Otomo, Takanobu; Nezu, Akiko; Hamasaki, Maho; Yoshimori, Tamotsu
Abstract: Autophagy is a multistep membrane traffic pathway. In contrast to autophagosome formation, the mechanisms underlying autophagosome–lysosome fusion remain largely unknown. Here, we describe a novel autophagy regulator, inositol polyphosphate‐5‐phosphatase E (INPP5E), involved in autophagosome–lysosome fusion process. In neuronal cells, INPP5E knockdown strongly inhibited autophagy by impairing the fusion step. A fraction of INPP5E is localized to lysosomes, and its membrane anchoring and enzymatic activity are necessary for autophagy. INPP5E decreases lysosomal phosphatidylinositol 3, 5‐bisphosphate (PI(3, 5)P2 ), one of the substrates of the phosphatase, that counteracts cortactin‐mediated actin filament stabilization on lysosomes. Lysosomes require actin filaments on their surface for fusing with autophagosomes. INPP5E is one of the genes responsible for Joubert syndrome, a rare brain abnormality, and mutations found in patients with this disease caused defects in autophagy. Taken together, our data reveal a novel role of phosphoinositide on lysosomes and an association between autophagy and neuronal disease. Synopsis: Phosphoinositide 5‐phosphatase INPP5E decreases lysosomal phosphatidylinositol 3, 5‐bisphosphate, thereby promoting cortactin‐mediated actin filament stabilization on lysosomes and thus autophagosome–lysosome fusion. INPP5E, a phosphoinositide 5‐phosphatase, localizes to lysosomes. Loss of INPP5E affects autophagosome–lysosome fusion, but not lysosomal function INPP5E decreases phosphatidylinositol 3, 5‐bisphosphate, one of the substrates of the phosphatase, on lysosomes. Cortactin‐mediated actin filament stabilization on lysosomes depends on low phosphatidylinositol 3, 5‐bisphosphate levels and is required for lysosome fusion with autophagosomes. INPP5E is one of the genes responsible for Joubert syndrome, and mutations found in patients cause defects in autophagy. Abstract : Phosphoinositide 5‐phosphatase INPP5E decreases lysosomal phosphatidylinositol 3, 5‐bisphosphate, thereby promoting cortactin‐mediated actin filament stabilization on lysosomes and thus autophagosome–lysosome fusion.